Diagonals of separately continuous multi-valued mappings (in Ukrainian) - V. V. Mykhaylyuk; O. V. Sobchuk; O. G. Fotiy (Математичні Студії, 2013)
We solve the problem on a construction of a separatelycontinuous mapping with the given diagonal, which is thepointwise limit of a sequence of continuous mappings withvalues in an equiconnected space. We construct an example of aclosed-valued separately continuous mapping $fcolon[0,1]^2multimap mathbb R$ with an everywhere discontinuousdiagonal. The example shows that the results on points of jointcontinuity for compact-valued separately continuous mappingscan not be generalized to the case of closed-valued mappings.